2016
DOI: 10.3847/0004-637x/826/2/139
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleus of the Planetary Nebula Egb 6 as a Post-Mira Binary*

Abstract: EGB 6 is a faint, large, ancient planetary nebula (PN). Its central star, a hot DAOZ white dwarf (WD), is a prototype of a rare class of PN nuclei associated with dense, compact emission-line knots. The central star also shows excess fluxes in both the near-infrared (NIR) and mid-infrared (MIR). In a 2013 paper, we used Hubble Space Telescope (HST) images to show that the compact nebula is a point-like source, located 0 16 (∼118 AU) from the WD. We attributed the NIR excess to an M dwarf companion star, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…2. We fit the continuum shape with our final photospheric model assuming interstellar reddening E(B − V) = 0.025 ± 0.005, in good agreement with the value derived by Bond et al (2016, E(B−V) = 0.02) and confirming the conclusion that the hot central star suffers no reddening within the system because the total reddening in the direction of EGB 6 is about E(B − V) = 0.027 (Schlafly & Finkbeiner 2011). From the Lyman lines, we derive an interstellar neutral hydrogen column density of log(n H /cm 2 )= 20.3 ± 0.4.…”
Section: Observationssupporting
confidence: 85%
See 2 more Smart Citations
“…2. We fit the continuum shape with our final photospheric model assuming interstellar reddening E(B − V) = 0.025 ± 0.005, in good agreement with the value derived by Bond et al (2016, E(B−V) = 0.02) and confirming the conclusion that the hot central star suffers no reddening within the system because the total reddening in the direction of EGB 6 is about E(B − V) = 0.027 (Schlafly & Finkbeiner 2011). From the Lyman lines, we derive an interstellar neutral hydrogen column density of log(n H /cm 2 )= 20.3 ± 0.4.…”
Section: Observationssupporting
confidence: 85%
“…It was suggested that it is the remnant of a disk containing material captured by the companion star from the WD progenitor's wind ⋆ Based on observations made with the NASA-CNES-CSA Far Ultraviolet Spectroscopic Explorer and the NASA/ESA Hubble Space Telescope, obtained at the Space Telescope Science Institute, which is operated by the Association of Universities for Research in Astronomy, Inc., under NASA contract NAS5-26666. during its asymptotic giant branch (AGB) stage, and that this disk is surrounded by gas (the CEK) photoionized by the hot WD. The nature of the companion is in fact unknown because it is enshrouded by dust (Bond et al 2016). It must be a lowluminosity object, a dM star or even another WD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that binary stellar systems (e.g, Bond & Livio 1990;Bond 2000;Zijlstra 2015) or planetary systems (e.g, De Marco & Soker 2011) shape planetary nebulae (PNe) has gained a huge support over the years, both from theoretical considerations that point to the difficulties of models based on single asymptotic giant branch (AGB) stellar progenitors to shape PNe (e.g., Soker & Harpaz 1992;Nordhaus & Blackman 2006;García-Segura et al 2014), and from a large number of observations and their analysis (e.g., from 2015 on, Akras et al 2015;Aller et al 2015a,b;Boffin 2015;Corradi et al 2015;Decin et al 2015;Douchin et al 2015;Fang et al 2015;Gorlova et al 2015;Hillwig et al 2015;Jones 2015;Jones et al 2015;Martínez González et al 2015;Miszalski et al 2015;Močnik et al 2015;Montez et al 2015;Jones et al 2016;Chiotellis et al 2016;Akras et al 2016;García-Rojas et al 2016;Jones 2016;Hillwig et al 2016a,b;Bond et al 2016;Chen et al 2016;Madappatt et al 2016;Ali et al 2016;Hillwig et al 2017). In most cases of shaping by binary interaction, jets are involved (e.g., Morris 1987;Soker 1990;Sahai & Trauger 1998;Boffin et al 2012;HuarteEspinosa et al 2012;…”
Section: Introductionmentioning
confidence: 99%
“…The high electron density of this knot (2.2x10 6 cm − 3) argues for a disk around the companion to the central star and suggests that the low mass companion has captured some material from the PN ejection process (Bond et al 2016). If JaFu 1 belongs to this class, then its binary nature would be even more compelling.…”
Section: +204mentioning
confidence: 99%